“Teaching Perspective Techniques in Fine Arts Lessons: Pedagogical and Scientific Foundations” - Qudratova Gulizuhro Otabek qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article explores the pedagogical and scientific foundations of teaching perspective techniques in fine arts lessons. Perspective is a crucial element in visual arts that enables students to depict depth, space, and proportion accurately. The study examines methods for teaching one-point, two-point, and multi-point perspective, integrating theoretical knowledge, practical exercises, and modern teaching technologies. Effective instruction in perspective develops students’ visual perception, compositional skills, and artistic creativity.